Х/12=45 -37 х-56=34/2 х+24=43*2 67-х=84/3 810/х=15*6

Х/12=45 -37 х-56=34/2 х+24=43*2 67-х=84/3 810/х=15*6
Гость
Ответ(ы) на вопрос:
Гость
х : 12 = 45 - 37              х - 56 = 34 : 2               х + 24 = 43 * 2 х : 12 = 8                        х - 56 = 17                    х + 24 = 86   х = 8 * 12                        х = 17 + 56                   х = 86 - 24 х = 96                              х = 73                            х = 62   96 : 12 = 45 - 37             73 - 56 = 34 : 2             62 + 24 = 43 * 2   67 - х = 84 : 3                  810 : х = 15 * 6 67 - х = 28                       810 : х = 90 х = 67 - 28                       х = 810 : 90       х = 39                               х = 9 67 - 39 = 84 : 3                810 : 9 = 15 * 6                 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы